Do texto literário para a literariedade das narrativas da Amazônia: uma proposta de ensino de leitura - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The literary artistic text is one of the most expressive instruments of collaboration in the formation of readers, because it carries a high quality and makes special use of the language, it has the great capacity of gives meaning to the world. It is necessary that the precious mission to train readers, genuinely attributed to school, should be carried out also through these texts, since they are constituted of knowledge about the world and man, capable of promoting intense experiences to the reader. Considering the relevance of the reading of literary artistic texts, in the school context, we tried to elaborate, apply and evaluate a reading practice of short stories about Brazilian Literature of Amazonian Expression. The objective of the methodological steps carried out here is to verify how Brazilian Literature of Amazonian Expression can contribute to the reader’s formation. Our target audience is the 8th grade elementary school students of the Nossa Senhora do Perpétuo Socorro Municipal School, observed here as beginning literary readers, capable of engaging in literary literacy practices within a critical and emancipatory perspective. The choice of this literary expression is due to its relevance to the characterization of this space, since the narratives approach and reflect in some way the social reality of the target audience of this intervention. This study made it possible to consolidate the knowledge of the process of constitution of the Brazilian Literature of Amazonian Expression, as well as its components, influencers and pioneers that allowed the sedimentation of a unique literature, capable of meaning the life of the students of this space. This reflection was based on the ideas TUPIASSU (2016), LOUREIRO (1995), SOUSA (2010), FARES (2014), JUNIOR (1969) BENCHIMOL (2014). The teaching proposal is based on the pedagogical knowledge proposed by SOUSA and GIROTO (2014), COSSON (2012) and SOLÉ (1998). The reflections presented here throw a reflexive look at how the literary artistic reading in the school and how it can be done in a contextualized way close to the social reality of the student.
Keywords: Leitura; Literatura; Leitor; Amazônica; Ensino; Realidade; CNPQ::CIÊNCIAS HUMANAS